Law and gender inequality the politics of women's rights in India - Flavia (New Delhi ; Oxford : Oxford University Press, 2001)
This volume provides an analysis of the current trends of debate on the Uniform Civil Code located within a highly charged and communally vitiated political scenario and goes on to expose the communal undertones of some recent judicial pronouncements.
Originally published: 1999.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Women -- India -- Social conditions; Women's rights -- India; Women -- Legal status, laws, etc. -- India